Quality of Life Among End-Stage Renal Disease Patients in Ilocos Sur, Philippines - Bautista, Leila Sylvia F.; Aquino, Maria Yolanda R. (South Eastern European Journal of Public Health, 2024)
Introduction: Life with End-Stage Renal Disease (ESRD) is a perpetual challenge due to the demanding treatment schedule and other aspects of life, including pain and the patient's dependence on a machine (dialysis) for survival, which conflicts with the independence needed to maintain a normal life. Objectives: The study determined the quality of life among ESRD patients and explored the association between the respondents’ quality of life and their socio-demographic and health-related profiles. Methods: The research utilized the descriptive-correlational design. The respondents comprised 147 patients who sought hemodialysis treatment in hemodialysis centers of the first district of Ilocos Sur, Philippines. Results: Results showed that ESRD patients enjoy an acceptable quality of life. They have a good physical ability to enjoy life and a psycho-spiritual ability to cope with the effects of the disease, average economic productivity, and effective and meaningful political, community, and social participation. Factors like age, sex, civil status, occupation, educational attainment, co-morbidities, and several times undergoing hemodialysis showed a significant relationship to a better quality of life. Conclusion: The study indicates that living with a chronic illness such as ESRD can significantly compromise what the patients hold, relating to what gives their lives quality and to what they attribute meaning in their lives. ESRD has a detrimental influence on every element or aspect of a patient's life.